2016
DOI: 10.1016/j.jns.2015.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged central sensory conduction time in patients with chronic arsenic exposure

Abstract: This is the first study to identify an impairment of the central somatosensory pathway in patients with chronic arsenic exposure. Sensory disturbance in these patients is related not only to peripheral neuropathy but also to impairment of the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…As mentioned above, several studies have shown that arsenic exposure induces peripheral neuropathy or neuritis [7, 9, 22–24]. A few studies have separately analyzed the function of small and large fibers, and suggested that these particular effects of arsenic are specific to small fibers [6, 9, 10]. Large-fiber function can be evaluated not only by neurological examination of vibration sensation but also by nerve conduction studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, several studies have shown that arsenic exposure induces peripheral neuropathy or neuritis [7, 9, 22–24]. A few studies have separately analyzed the function of small and large fibers, and suggested that these particular effects of arsenic are specific to small fibers [6, 9, 10]. Large-fiber function can be evaluated not only by neurological examination of vibration sensation but also by nerve conduction studies.…”
Section: Discussionmentioning
confidence: 99%
“…At least 140 million people in more than 50 countries are exposed to arsenic-contaminated drinking water [3]. Chronic arsenic toxicity induces not only cardiovascular disease, skin lesions, diabetes, and cancers of the kidney, skin, and bladder [1, 4, 5] but also central and peripheral nervous system impairments [69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy could not be explained solely by the age-related impairment of large peripheral nerves. Indeed, two studies that evaluated sensory disturbance in residents of Toroku demonstrated central nervous system dysfunction (Mochizuki et al 2016 ) and small fiber neuropathy (Kawasaki et al 2002 ). Although the detailed mechanisms are unclear, these conditions may have contributed to the gradual sensory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, huge amounts of arsenic trioxide-containing gases were leaked from the roasters and intermittently covered the entire Toroku valley, causing both refinery workers and residents to be exposed to arsenic orally (via contaminated food and water), dermally, or tracheally (via contaminated air) (Miyazaki prefecture 1972 ; Tsuda et al 1990 ). The polluted environment caused chronic arsenic intoxication in many workers and residents, leading to many deaths before 1962 (Miyazaki prefecture 1972 ; Mochizuki et al 2016 ). In 1972, 10 years after the mine closed, arsenic concentrations were finally measured by Miyazaki prefecture.…”
mentioning
confidence: 99%